Reconstructing the timescale of a catastrophic fan‐forming event on Earth using a Mars model. Issue 23 (14th December 2015) - Duller, Robert A.; Warner, Nicholas H.; De Angelis, Silvio; Armitage, John J.; Poyatos‐Moré, Miquel
Abstract: The calculation of formation timescales of alluvial fans and deltas on Mars is important as it has direct implications for understanding the planet's hydrologic history. The robustness of sediment transport models is not in doubt but validation of the broad approach using a terrestrial example of similar scale and likely origin, where hydraulic parameters and timescales are known, is useful. Using a catastrophically formed terrestrial fan, where abundant sedimentological information is available, we find that the modeled hydraulic parameters and formation timescales are in very close agreement with the known values of the event. This supports the general modeling approach as applied to Mars fans but also highlights the added value of detailed sedimentary information when reconstructing hydraulics and timescales on Earth and Mars, which cannot be confidently gleaned from the final snapshot of surface geomorphology alone. Key Points: Sedimentology constrained key parameters and the choice of key transport relationships A Mars approach to calculate fan formation timescales is validated by an Earth example Sedimentary information will reduce the uncertainty in the timescale calculation